Heterogeneity of histopathological presentation of pilocytic astrocytoma – diagnostic pitfalls. A review - Matyja, Ewa; Grajkowska, Wiesława; Stępień, Katarzyna; Naganska, Ewa (Folia Neuropathologica, 2016)
Pilocytic astrocytomas (PAs) are the most frequent primary astroglial tumours affecting children and adolescents. They occur sporadically or in association with a genetically determined syndrome – neurofibromatosis type 1. Classic PA usually manifests as a well-circumscribed, often cystic, slowly growing tumour, which corresponds to WHO grade I. The majority of pilocytic tumours arise along the neuraxis, predominantly in the cerebellum. They are associated with favourable long-term outcome or spontaneous regression, even after incomplete resection. However, the behaviour and prognosis might also be related to tumour histology and location. Pilomyxoid astrocytoma (PMA) represents a variant of classical PA with more invasive growth and increased risk of recurrences and dissemination. Typically, PAs exhibit distinct histology with biphasic architecture of loose, microcystic and compact, fibrillary areas. However, some tumours arise in an uncommon location and display heterogeneous histopathological appearance. The morphological pattern of PA can mimic some other glial neoplasms, including oligodendroglioma, pleomorphic xanthoastrocytoma, ependymoma or diffuse astrocytoma. Not infrequently, the advanced degenerative changes, including vascular fibrosis, and recent and old haemorrhages, may mimic vascular pathology. Sometimes, the neoplastic piloid tissue can resemble reactive gliosis, related to long-standing non neoplastic lesions. Not infrequently, PA exhibits histological features typical for anaplasia, including necrosis, mitoses and glomeruloid vascular proliferation that can suggest a diffuse high-grade glioma. However, even those PAs that lack distinct histological features of anaplasia can behave unpredictably, in a more aggressive manner, with leptomeningeal spreading. Genetic alterations resulting in aberrant signalling of the mitogen-activated protein kinase (MAPK) pathway have been considered to underlie the development of PAs. The most commonly identified KIAA1549-BRAF fusion is important for appropriate tumour molecular diagnosis. In this paper we summarize the clinicopathological presentation of PAs, with emphasis on their heterogeneous morphology, based on our own experience in the field of surgical neuropathology and the literature data. Diagnosis of pilocytic tumours requires careful analysis of clinical, histopathological and molecular features to avoid misinterpretation of these benign neoplastic lesions.